Coal optimism: carbon ideologies and the good lives of extraction. Issue 3 (4th March 2021) - Krieg, C. Parker
ABSTRACT: This essay argues that a persistent structure of feeling in the literature and cultural politics of coal extraction in the United States can be described by Lauren Berlant's concept of 'cruel optimism'. This contradictory desire for an object which materially prevents the flourishing it promises is evident in the case of the fossil energies, which are invested with late Fordist fantasies of stabilisation at the same time that climate change renders them untenable. It explores this 'coal optimism' through William T. Vollmann's two-volume Carbon Ideologies, and recent novels by Tawni O'Dell and Carter Sickels, each of which call into question the utility of affect in the context of energy and climate discourse.